Analisis Konsentrasi PM2,5, CO dan CO2 di Dalam Ruangan Akibat Penggunaan Kompor Biomassa Berbahan Bakar Briket Tempurung Kelapa dan Briket Kayu Bakar - Fadjar Goembira; Afifah Nazir; Amalia Husna; Taufiq Ihsan (Universitas Andalas, 2019)
The objective of this study was to analyze the concentration of PM2.5, CO and CO2 indoor due to the use of biomass stoves and to calculate the value of combustion efficiency and fuel use efficiency in biomass stoves. The test was conducted by the water boiling test method to simulate the cooking process that was divided into 3 phases. The fuel used was coconut shell briquettes and firewood briquettes. Based on the test results the obtained concentration of PM2.5 from the the use of coconut shell briquette was 21.03 µg/Nm3 during the cold start phase, 23.66 µg/Nm3 in the hot start phase, and 15.57 µg/Nm3 in the simmering phase. As for Firewood briquette, it had lower PM2.5 concentrations, i.e., 17.17 µg/Nm3 in the cold start phase, 20.63 µg/Nm3 in the hot start phase, and 12.17 µg/Nm3 in the simmering phase. The results of CO concentration measurement in coconut shell briquette for the cold start, hot start, and simmering phases were 4.57; 4.32 and 5.27 ppm, respectively, and for firewood briquette were 3.92; 3.69 and 4.61 ppm, correspondingly. While for CO2 concentration measurements, for coconut shell briquette at cold start, hot start, and simmering phases were 376.83; 364.56 and 443.11 ppm, respectively, and for firewood briquette were 397.4; 383.61 and 486.45 ppm, accordingly. The concentration of PM2.5, CO and CO2 did not exceed the indoor air quality standard regulated by the Minister of Health Regulation No. 1077 of 2011 which is 35 µg/Nm3 for PM2.5, 9 ppm for CO and 1,000 ppm for CO2. The ratio of the biomass stove CO / CO2 briquette fuel was below the value of 0.02 which means that the combustion process occurred perfectly. The efficiency value of coconut shell briquette combustion was lower than that of firewood briquette combustion which is influenced by heating value, water temperature, the amount of fuel used and the length of the testing process, while the efficient use of fuel from using briquettes was better than biomass stoves made from unprocessed/raw biomass fuels.